Differential Effects of Oleic and Palmitic Acids on Lipid Droplet-Mitochondria Interaction in the Hepatic Cell Line HepG2 - Eynaudi, Andrea; Díaz-Castro, Francisco; Bórquez, Juan Carlos; Bravo-Sagua, Roberto; Parra, Valentina; Troncoso, Rodrigo (Frontiers in Nutrition, 2021)
Fatty acid overload, either of the saturated palmitic acid (PA) or the unsaturated oleic acid (OA), causes triglyceride accumulation into specialized organelles termed lipid droplets (LD). However, only PA overload leads to liver damage mediated by mitochondrial dysfunction. Whether these divergent outcomes stem from differential effects of PA and OA on LD and mitochondria joint dynamics remains to be uncovered. Here, we contrast how both fatty acids impact the morphology and interaction between both organelles and mitochondrial bioenergetics in HepG2 cells. Using confocal microscopy, we showed that short-term (2-24 h) OA overload promotes more and bigger LD accumulation than PA. Oxygen polarography indicated that both treatments stimulated mitochondrial respiration; however, OA favored an overall build-up of the mitochondrial potential, and PA evoked mitochondrial fragmentation, concomitant with an ATP-oriented metabolism. Even though PA-induced a lesser increase in LD-mitochondria proximity than OA, those LD associated with highly active mitochondria suggest that they interact mainly to fuel fatty acid oxidation and ATP synthesis (that is, metabolically “active” LD). On the contrary, OA overload seemingly stimulated LD-mitochondria interaction mainly for LD growth (thus metabolically “passive” LDs). In sum, these differences point out that OA readily accumulates in LD, likely reducing their toxicity, while PA preferably stimulates mitochondrial oxidative metabolism, which may contribute to liver damage progression.